Analysis on export competitiveness of oilseeds with BRICS countries: Analysis on export competitiveness of oilseeds with BRICS countries - S R DEVEGOWDA,; P S BADAL,; AVDHESH SHARMA, (Journal of Oilseeds Research, 2020)
The paper attempts to assess India’s trade intensity as well as the revealed comparative advantage (RCA) of theoilseeds with respect to trade with BRICS (Brazil, Russia, India, China and South Africa) disaggregate levels. Thestudy assesses the structure of the comparative advantage from 2001 to 2018. The study found that TI (Trade Intensity) with the BRICS group was more in comparison to ROW (Rest of world). EEI (Export Intensity Index) for BRICS countries was also more intense in comparison to ROW whereas III (Import Intensity Index) showed less intense in comparison to ROW. Relative comparative advantage for groundnut, sesame and mustard was observed with the BRICS group.